2007
DOI: 10.1007/s11430-007-0120-y
|View full text |Cite
|
Sign up to set email alerts
|

Mass budgets of the Lambert, Mellor and Fisher Glaciers and basal fluxes beneath their flowbands on Amery Ice Shelf

Abstract: respectively. We find a much larger total basal melting and net melting than the results for the whole Amery Ice Shelf derived from previous modeling and oceanographic measurements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
59
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(75 citation statements)
references
References 58 publications
(130 reference statements)
11
59
5
Order By: Relevance
“…Since the airborne RES signals may not penetrate a basal marine ice layer [ Fricker et al , 2001], we also estimated the ice thickness for the floating ice shelf based on a hydrostatic equilibrium model [ Fricker et al , 2001; Joughin and Padman , 2003] applied to the ICESat laser altimetry data. In our hydrostatic calculation, the column‐averaged ice density value varies from the ice shelf front to the grounding zone in the range of 890.5–921.0 kg m −3 as in the work of Wen et al [2007]. The comparison of the hydrostatic ice thickness estimates with airborne RES ice thickness measurements confirms the existence of an extensive marine ice layer in the downstream section of the ice shelf as reported by Fricker et al [2001], Wang et al [2006], Wen et al [2007], Craven et al [2009], and Wen et al [2010].…”
Section: Mass Balance Analysismentioning
confidence: 99%
See 4 more Smart Citations
“…Since the airborne RES signals may not penetrate a basal marine ice layer [ Fricker et al , 2001], we also estimated the ice thickness for the floating ice shelf based on a hydrostatic equilibrium model [ Fricker et al , 2001; Joughin and Padman , 2003] applied to the ICESat laser altimetry data. In our hydrostatic calculation, the column‐averaged ice density value varies from the ice shelf front to the grounding zone in the range of 890.5–921.0 kg m −3 as in the work of Wen et al [2007]. The comparison of the hydrostatic ice thickness estimates with airborne RES ice thickness measurements confirms the existence of an extensive marine ice layer in the downstream section of the ice shelf as reported by Fricker et al [2001], Wang et al [2006], Wen et al [2007], Craven et al [2009], and Wen et al [2010].…”
Section: Mass Balance Analysismentioning
confidence: 99%
“…In our hydrostatic calculation, the column‐averaged ice density value varies from the ice shelf front to the grounding zone in the range of 890.5–921.0 kg m −3 as in the work of Wen et al [2007]. The comparison of the hydrostatic ice thickness estimates with airborne RES ice thickness measurements confirms the existence of an extensive marine ice layer in the downstream section of the ice shelf as reported by Fricker et al [2001], Wang et al [2006], Wen et al [2007], Craven et al [2009], and Wen et al [2010]. The RES ice thickness measurements are used for the fluxgates located in the grounding zone, where we found that hydrostatically derived ice thickness values were not reliable, apparently because the hydrostatic equilibrium condition was not satisfied.…”
Section: Mass Balance Analysismentioning
confidence: 99%
See 3 more Smart Citations